„Blaski Miltonowskiego utraconego raju”. Obraz przeszłości w pisarstwie Henryka Sienkiewicza - Adamek-Świechowska, Adrianna (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
The article deals with the analysis of the artistic and the ideological assumptions of the constructing the literary image of the past in point of view of Henryk Sienkiewicz in connection with his polemic against Włodzimierz Spasowicz in the context of the discussion of the 19th-century about the values of historical novel. In the theoretical declarations the author pays major attention to the hypnotic charm of the past which he named „the brilliane of Milton’s paradise lost” and references to the great poetry of romanticism. In the writer;s programme intentions the literary works should presented the ideological versions of the myth of the Polish past during the period of national slavery. Sienkiewicz focuses on subjective experiences of his fictional heroes, connects existential and historical dimensions of human life, looking for semantic mechanisms of history. The analysis of the writer’s outlook on life concentrating on the universal questions like the sense of life, the essence of world, the human’s nature and the hierarchy of values. The article attempts to show that the absolute values existence depends on the memory of the past.